Healthy Homes vs. Urban Micro-Drainage: A Promotion Issue in Brazilian Towns and Cities - Teixeira, Maria da Purificação (2015)
Current study underscores the best appropriation of Healthy Homes as an important factor in decision-taking within municipal administration. Home adequacy is a strategy in health promotion and associates the adequacy of homes to sanitation, with special attention to rain water management in tropical regions. Methodology deals with the multidisciplinary treatments within co-relationships undertaken by different areas of knowledge on the theme and the later analysis by multi-criteria investigation. A dynamic factor for environmental primary attendance is provided, associated to primary attention to health, within the strategies called Healthy Homes or the Home as Health Promoter. Strategies present the initial discussion on Home as Health Promoter from the Urban Micro-drainage trend.